PENGARUH SUKUK, REKSADANA SYARI’AH DAN INFLASI TERHADAP TINGKAT PEREKONOMIAN INDONESIA PERIODE 2011-2020 - Muttaqien, Muhammad Izzia Thoriq (Islamic Economics and finance in Focus, 2022)
This study aims to determine and analyze the effect of sukuk, sharia mutual funds and inflation on Indonesia's economic level for the period 2011-2020. Here the data that the authors take is data on Sukuk, Sharia Mutual Funds, Inflation and Economic Level in 2011-2020 for the quarterly period. This study uses the multiple linear regression method to test the hypothesis with statistical analysis tools in the form of SPSS Version 21 software. Hypothesis testing is carried out after the multiple linear regression model to be used is considered feasible or free from violations of classical assumptions so that the test results can be interpreted correctly. Classical assumption test includes normality test, multicollinearity test, heteroscedasticity test. The results in this study show that sukuk have a significant effect on Indonesia's economic level in 2011-2020 for the quarterly period. Sharia mutual funds have a significant effect on Indonesia's economic level in 2011-2020 quarterly period, Inflation has a significant effect on Indonesia's economic level in 2011-2020 quarterly period.